2014
DOI: 10.1002/cbdv.201300151
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal Triterpenes from Lantana camara

Abstract: Two new natural triterpenes, lantaninilic acid and lantoic acid, along with the known triterpenes lantadene A, and oleanolic, ursolic, betulinic, lantanolic, and camaric acid, were obtained from the aerial parts of Lantana camara through bioassay-guided isolation, monitoring the in vitro antileishmanial activity against promastigotes of Leishmania major. Oleanolic acid (3), ursolic acid (4), lantadene A (5), and lantanilic acid (7) showed significant leishmanicidal activities with IC50 values of 53.0, 12.4, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Thenematicidal activities against Meloidogyne incognita of aMeOH extract of L. camara,its fractions, and various pure compounds have been reported by us in earlier studies [7][10] [11].Inthe present investigation, anew triterpenoid lactone,lancamarolide( 1), along with oleanonic acid (2) [ 12], lantadene A( 3) [ 13], 11a-hydroxy-3oxours-12-en-28-oic acid (4) [ 14], betulinic acid (5) [ 15], lantadene B( 6) [ 16], and lantaninilic acid (7) [17] (Fig. 1)were isolated from L. camara.All of thesecompounds were examinedf or theirn ematicidal activities against M. incognita,t he root-knot nematode.…”
supporting
confidence: 61%
“…Thenematicidal activities against Meloidogyne incognita of aMeOH extract of L. camara,its fractions, and various pure compounds have been reported by us in earlier studies [7][10] [11].Inthe present investigation, anew triterpenoid lactone,lancamarolide( 1), along with oleanonic acid (2) [ 12], lantadene A( 3) [ 13], 11a-hydroxy-3oxours-12-en-28-oic acid (4) [ 14], betulinic acid (5) [ 15], lantadene B( 6) [ 16], and lantaninilic acid (7) [17] (Fig. 1)were isolated from L. camara.All of thesecompounds were examinedf or theirn ematicidal activities against M. incognita,t he root-knot nematode.…”
supporting
confidence: 61%
“…The diversity of triterpenes is highly associated with their broad range of pharmacological effects, and different studies have already shown that these compounds present multispecies action against Leishmania sp. (Gnoatto et al., 2008, Bero et al., 2011, Begum et al., 2014). Recently, it was demonstrated that ursolic acid (UA) displayed activity against promastigote and amastigote forms of L. (L.) amazonensis , L. (V.) braziliensis , L. (L.) chagasi , and L. (L.) major (Passero et al., 2011, Begum et al., 2014, Yamamoto et al., 2014, Yamamoto et al., 2015), suggesting that UA presents multispectral action.…”
Section: Introductionmentioning
confidence: 99%
“…(Gnoatto et al., 2008, Bero et al., 2011, Begum et al., 2014). Recently, it was demonstrated that ursolic acid (UA) displayed activity against promastigote and amastigote forms of L. (L.) amazonensis , L. (V.) braziliensis , L. (L.) chagasi , and L. (L.) major (Passero et al., 2011, Begum et al., 2014, Yamamoto et al., 2014, Yamamoto et al., 2015), suggesting that UA presents multispectral action. In spite of that, few works have performed in vivo studies in order to evaluate the therapeutic potential of this triterpene and, more importantly, up to now there has not been any report analyzing the therapeutic action of this compound on VL, one of the most important medical conditions caused by Leishmania parasites.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical shifts and their assignments reported by Siddiqui are summarized in Table . Years after this work, more studies have been conducted on 1 and 2 , and they refer to Siddiqui's article for spectral assignments . However, our analysis indicated that eight signals were wrongly assigned.…”
Section: Resultsmentioning
confidence: 99%
“…Years after this work, more studies have been conducted on 1 and 2, and they refer to Siddiqui's article for spectral assignments. [6][7][8][9][10][11][12][13][14][15][16] However, our analysis indicated that eight signals were wrongly assigned.…”
Section: Resultsmentioning
confidence: 99%